Sorting, Selection, and Transformation of the Return to College Education in China - Belton M. Fleisher; Haizheng Li; Shi Li; Xiaojun Wang (Institute for the Study of Labor (IZA), 2004)
We estimate selection and sorting effects on the evolution of the private return to schooling for college graduates during China?s between 1988 and 2002. We pay special attention to the changing role of sorting by ability versus budget-constraint effects as China?s education policy has changed from one in which the bulk of direct costs are paid by government for students who pass a rigid set of test to one in which freedom of choice is increasingly the rule for those who can afford to pay for tuition and living expenses while acquiring higher education. We find evidence of substantial sorting gains under the traditional system but that gains have diminished and even become negative as schooling choices widened and participation has become subject to increasing direct private costs. We take this as evidence consistent with the influence of financial constraints on decisions to attend college.
Keywords: O15; J24; J31; 330; return to schooling; sorting gains; heterogeneity; financial constraints; comparative advantage; Bildungschancen; Bildungsverhalten; Studium; Bildungsertrag; Studienfinanzierung; Schätzung; China